Epoxy resin composition, electronic component mounting structure, and method for manufacturing the same

CN110651007BActive Publication Date: 2026-10-30NAGASE CHEMTEX CORPORATION
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN201880033290.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2017-06-09
Filing Date
2018-05-30
Publication Date
2026-10-30
Estimated Expiration
2038-05-30

AI Technical Summary

Benefits of technology

[0016]根据本发明,能够提供在固化后被研磨时可形成平坦性高的研磨面的环氧树脂组合物。另外,根据本发明,能够提供具有平坦性高的研磨面的电子部件安装结构体。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN110651007B_ABST
    Figure CN110651007B_ABST
Patent Text Reader

Abstract

The present invention provides an epoxy resin composition having a high flatness of a polished surface obtained by polishing a surface after curing, and a manufacturing method of an electronic component mounting structure having a high flatness of a polished surface obtained by polishing a surface of a sealing body. The present invention relates to an epoxy resin composition containing an epoxy resin, fused silica which can contain hollow particles, and a curing agent, an electronic component mounting structure using the above-described epoxy resin composition, and a manufacturing method thereof, wherein, in a polished surface obtained by polishing a cured product of the above-described epoxy resin composition, the number of holes having a diameter of greater than 5 μm, which is observed in a cross section derived from the above-described hollow particles, is one or less in a range of 25 mm 2 or less, and a coating material is applied to the above-described polished surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to epoxy resin compositions, electronic component mounting structures, and methods for manufacturing the same. Background Technology

[0002] In recent years, the demand for thinner and smaller semiconductor products has led to increased attention on packaging technologies known as panel-level packaging (PLP) and wafer-level packaging (WLP). Among PLP and WLP, fan-out panel-level packaging (FOPLP) and fan-out wafer-level packaging (FOWLP) can achieve a larger mounting area than the semiconductor chip itself because they can form redistribution lines extending to the outside of the semiconductor chip. Since FOPLP or FOWLP does not use a packaging substrate, it is thinner than conventional semiconductor products, and the shorter wiring lengths also allow for higher transmission speeds.

[0003] For semiconductor sealing materials, requirements include electrical insulation, heat resistance, and moisture resistance. The mainstream approach is to use a combination of curable epoxy resin and inorganic materials known as fillers. By increasing the filler content, the thermal expansion coefficient of the semiconductor sealing material can be kept relatively low.

[0004] In the pursuit of thinner designs by grinding cured semiconductor sealing materials, a high degree of flatness is required on the ground surface. Patent Document 1 proposes a technique in which, after forming an insulating resin layer on a wafer of a functional element, a resin layer called a sacrificial layer is applied, followed by grinding or polishing of the insulating resin layer and the sacrificial layer to flatten the surface. The sacrificial layer is then removed.

[0005] Existing technical documents

[0006] Patent documents

[0007] Patent Document 1: Japanese Patent Publication No. 2013-528318 Summary of the Invention

[0008] The problem that the invention aims to solve

[0009] With the increasing functionality of electronic devices, high-density wiring is required in semiconductor products. The circuit width / spacing (L / S) of redistribution layers has reached 5μm / 5μm, and there is a trend towards further miniaturization. In assembly methods where a redistribution layer is formed on a flat substrate, followed by flip-chip bonding and resin sealing, the wiring pattern is generally relatively stable. On the other hand, when a redistribution layer is formed on a polished surface after resin sealing of electronic components such as semiconductor devices, a high degree of flatness is required on the polished surface to form a fine redistribution layer. Even in assembly methods where a redistribution layer is formed on a flat substrate and then flip-chip bonding and resin sealing are performed, where redistribution layers are formed on both sides, the polished surface is similarly required to have a high degree of flatness because the other redistribution layer is formed by polishing the surface of the sealant.

[0010] However, when grinding cured semiconductor sealing materials, pores and unevenness sometimes form on the ground surface. It is believed that this unevenness is caused by filler shedding, etc. Theoretically, while reducing the filler particle size can reduce the unevenness originating from the filler, miniaturizing the filler further reduces workability due to the increased viscosity of the semiconductor sealing material, thus limiting its content; miniaturization has its limits. In other words, suppressing unevenness on the ground surface by controlling the filler particle size is difficult.

[0011] Methods for solving problems

[0012] One aspect of the present invention relates to an epoxy resin composition comprising an epoxy resin, fused silica which may contain hollow particles, and a curing agent and / or a curing accelerator, wherein a polished surface obtained by grinding the cured epoxy resin composition comprises a surface with a diameter of 25 mm. 2 The number of pores with a diameter greater than 5 μm from the cross-section of the aforementioned hollow particles observed within the range was less than one.

[0013] Another aspect of the present invention relates to an electronic component mounting structure comprising an electronic component or substrate, and a cured epoxy resin composition sealing the electronic component or substrate, wherein the epoxy resin composition comprises epoxy resin, fused silica which may contain hollow particles, and a curing agent and / or a curing accelerator, and the cured product has a polished surface, wherein in the polished surface, within 25 mm... 2 The number of pores with a diameter greater than 5 μm from the cross-section of the aforementioned hollow particles observed within the range was less than one.

[0014] Another aspect of the present invention relates to a method for manufacturing an electronic component mounting structure, comprising the following steps: a step of preparing an electronic component or substrate and the aforementioned epoxy resin composition; a step of sealing the electronic component or substrate with the aforementioned epoxy resin composition while simultaneously curing the aforementioned epoxy resin composition to form a sealed body comprising the aforementioned electronic component or substrate and the aforementioned epoxy resin composition; a step of grinding a portion of the aforementioned cured body to form a ground surface; and a step of forming a redistribution layer on the aforementioned ground surface.

[0015] Invention Effects

[0016] According to the present invention, an epoxy resin composition can be provided that can form a highly flat polished surface when polished after curing. Furthermore, according to the present invention, an electronic component mounting structure having a highly flat polished surface can be provided. Attached Figure Description

[0017] Figure 1 The image is an image obtained by taking a super-depth color 3D shape measurement microscope on the polished surface obtained in Example 1, and is a diagram showing the holes in the cross section originating from hollow particles.

[0018] Figure 2 The image is an image obtained by taking a super-depth color 3D shape measurement microscope on the polished surface obtained in Example 2, and is a diagram showing the holes in the cross section originating from hollow particles.

[0019] Figure 3 The image is an image obtained by taking a super-depth color 3D shape measurement microscope on the polished surface obtained in Example 3, and is a diagram showing the holes in the cross section originating from hollow particles.

[0020] Figure 4 The image is an image obtained by taking a super-depth color 3D shape measuring microscope on the polished surface obtained in Comparative Example 1, and is a diagram showing the holes in the cross section originating from hollow particles.

[0021] Figure 5 The image is an image obtained by using an ultra-deep color 3D shape measuring microscope to capture the polished surface obtained in Comparative Example 2. It is a diagram showing the holes in the cross-section of the hollow particles.

[0022] Figure 6 The image is an image obtained by taking a super-depth color 3D shape measurement microscope on the polished surface obtained in Comparative Example 3, and is a diagram showing the holes in the cross section originating from hollow particles. Detailed Implementation

[0023] The epoxy resin composition according to embodiments of the present invention comprises epoxy resin, fused silica which may contain hollow particles, and a curing agent and / or curing accelerator. In a polished surface obtained by grinding a cured epoxy resin composition, at a thickness of 25 mm... 2 Within the observed range, the number of pores with a diameter greater than 5 μm originating from the cross-section of hollow particles is 1 or less, preferably 0.1 or less, and more preferably there are virtually no pores with a diameter greater than 5 μm. Such a polished surface, having almost no micro-unevenness, is suitable for forming films of coating materials, for example, used to form redistribution layers. When a coating material is applied to a polished surface with high flatness, the flatness is inherited by the film of the coating material, and the flatness of the film surface also increases.

[0024] It should be noted that the hole originating from the cross-section of a hollow particle is not a through hole, but rather refers to a hollow depression originating from the hollow particle. Furthermore, when the hole is not circular, the maximum diameter of the hole is considered its diameter.

[0025] In the polished surface of the cured epoxy resin composition, at 25mm 2 The number of pores originating from the cross-section of hollow particles observed within a certain range can be determined, for example, using an ultra-deep color 3D shape measuring microscope (e.g., KEYENCE CORPORATION VK-9510). Specifically, this can be achieved by randomly selecting a 25mm section from the polished surface. 2 Within 10 regions of the range, the diameter and number of pores originating from the cross-section of hollow particles are measured, and the average number of pores of a specified size is calculated. The diameter or maximum diameter of the pores can also be measured using the same apparatus.

[0026] Spherical fused silica is, for example, silica obtained by melting pulverized silica powder in a high-temperature flame and spherizing it by surface tension. By incorporating gas during the melting process, hollow particles containing hollow sections are generated as a byproduct. Therefore, the cured epoxy resin composition may contain hollow particles. If the cured composition containing hollow particles is ground, pores originating from the cross-sections of the hollow particles are formed in the ground surface. The presence of these pores creates fine irregularities on the ground surface. Therefore, controlling the formation of hollow particles is effective in preventing the formation of these fine irregularities.

[0027] In the polished surface of the cured epoxy resin composition, the measurement was performed at 25 mm. 2 When determining the number of pores originating from the cross-section of hollow particles observed within a certain range, it is sufficient to heat-cure the epoxy resin composition at, for example, 150°C for 1 hour to form a cured product. Before heat-curing at 150°C for 1 hour, it may be heated at 100–125°C for 10–20 minutes, for example.

[0028] The method for forming the polished surface is not particularly limited, but it is preferable to polish the cured material until a region with a surface roughness (arithmetic mean roughness: Ra) of 0.2 μm or less is formed. The surface roughness can be measured in the region of the polished surface that does not have a hole with a diameter greater than 1.5 μm. The surface roughness can be measured as a line roughness with a measurement distance of 100 μm according to JIS B0601 (1994), for example, by using an ultra-deep color 3D shape measuring microscope (e.g., KEYENCE CORPORATION VK-9510).

[0029] Epoxy resin compositions can be used as sealing materials for electronic components. In particular, epoxy resin compositions are suitable as compression molding materials for sealing applications such as PLPs and WLPs. However, the molding method is not limited to compression molding; it can also include printing molding, transfer molding, coating molding using a dispenser, etc. Such molding materials include liquid epoxy resin compositions, semi-cured epoxy resin compositions (so-called B-stage), epoxy resin compositions molded into sheets, and epoxy resin compositions granulated into particles.

[0030] The coating material can be a material for forming rewires. In FOWLP (Foil-on-Plane Processing) within WLP (White-on-Plane Processing) or FOPLP (Foil-on-Plane Processing) within PLP (Plane-on-Plane Processing), a fine rewire layer is formed on the polished surface. When the rewire forming material is coated on a polished surface with almost no micro-unevenness and high flatness, the flatness of the film surface of the rewire forming material also increases. Therefore, it becomes easier to form a fine rewire layer more accurately on the polished surface, and it is less likely to cause rewire breakage.

[0031] The epoxy resin composition described in this embodiment is suitable for sealing large-area electronic components or substrates. Furthermore, the epoxy resin composition is also suitable as a sealing material (molding underfill material) for cases where electronic components or substrates equipped with semiconductor elements are underfilled and molded together. It should be noted that in this embodiment, the term "substrate" refers to a substrate containing electronic components, an assembly of electronic components, or the electronic components themselves.

[0032] Large-area substrates can be used to form packages such as wafer-level packaging (WLP) or panel-level packaging (PLP). Among these, FOPLP and FOWLP are attracting attention due to their ability to form larger redistribution layers. A large-area substrate can be a wafer with a diameter of 200mm (8 inches) or more, or a diameter of 300mm (12 inches) or more, and an area of ​​30,000 mm². 2The above refers to panels or wafers with dimensions of 300mm square or larger (e.g., 320mm × 320mm) or 400mm square or larger (e.g., 410mm × 515mm, 508mm × 610mm, 500mm × 510mm, 610mm × 457mm). The area of ​​each side of the substrate sealed with the epoxy resin composition need to be, for example, 90% or more of the substrate area; it can be single-sided or double-sided sealing.

[0033] In addition to wafers and panels, substrates also include glass substrates, resin substrates, and printed circuit board substrates containing electronic components. Examples of wafers include silicon wafers, sapphire wafers, and compound semiconductor wafers. Examples of resin substrates include bismaleimide triazine substrates, polyimide substrates, and fluoropolymer substrates.

[0034] In the polished surface obtained by grinding the cured epoxy resin composition, at 25mm 2 Within the observed range, the number of pores with a diameter greater than 5 μm originating from the cross-section of hollow particles is 1 or less, more preferably 0.1 or less, and most preferably substantially non-existent. Furthermore, the number of pores with a diameter greater than 3 μm is preferably 1 or less, more preferably 0.1 or less, and most preferably substantially non-existent. Moreover, the number of pores with a diameter greater than 2 μm is preferably 2 or less, more preferably 1 or less, even more preferably 0.1 or less, and most preferably substantially non-existent. Therefore, it becomes easier to form a redistribution layer with a circuit width / circuit spacing (L / S) finer than 2 μm / 2 μm on the polished surface.

[0035] It should be noted that a 25mm diameter was randomly selected from the polished surface of the cured product obtained by heat curing the epoxy resin composition at 150°C for 1 hour. 2 If no pores with a diameter greater than 5 μm (or pores with a diameter greater than 3 μm, or pores with a diameter greater than 2 μm) are observed in any of the 10 regions within the range, the epoxy resin composition can be considered to substantially not contain hollow particles with a diameter greater than 5 μm (or 3 μm or 2 μm).

[0036] Secondly, the electronic component mounting structure according to embodiments of the present invention includes an electronic component or substrate, and a cured epoxy resin composition that seals the electronic component or substrate. The electronic component may be, for example, a device containing a semiconductor chip, but is not particularly limited thereto. The cured epoxy resin composition has a polished surface.

[0037] In the polished surface, the arithmetic mean roughness (Ra) is preferably 0.2 μm or less, more preferably 0.15 μm or less.

[0038] Secondly, the method for manufacturing an electronic component mounting structure according to the embodiments of the present invention includes: (i) a step of preparing an electronic component or substrate and the above-mentioned epoxy resin composition; (ii) a step of sealing the electronic component or substrate with the epoxy resin composition while curing the epoxy resin composition to form a sealed body containing the electronic component or substrate and the epoxy resin composition; (iii) a step of grinding a portion of the cured body to form a polished surface; and (iv) a step of forming a coating material film or a redistribution layer on the polished surface.

[0039] The following example illustrates the use of epoxy resin compositions as compression molding materials (sealing materials) for FOPLP or FOWLP.

[0040] Process (i)

[0041] As an electronic component, it is an assembly of multiple monolithic semiconductor chips arranged on a resin film. Such an assembly is prepared, for example, by cutting semiconductor wafers into monolithic pieces and then placing them on a resin film.

[0042] The epoxy resin composition is prepared as a composition comprising epoxy resin, molten silica which may contain hollow particles, and a curing agent and / or a curing accelerator.

[0043] Process (ii)

[0044] Sealing electronic components using epoxy resin compositions can be achieved, for example, by compression molding. However, the molding method is not limited to compression molding; it can also include printing molding, transfer molding, coating molding using a dispenser, etc. In compression molding, for example, the electronic component and the epoxy resin composition are placed in a mold, and the epoxy resin composition is heated under a specified pressure. The epoxy resin composition is then cured to form a seal.

[0045] There are no particular limitations on the curing conditions, but for full curing, heating (heating during molding) and post-curing are preferred.

[0046] Heating (heating during forming) varies depending on the forming method, but is preferably carried out at 50–200°C, more preferably at 70–180°C. The heating time varies depending on the forming method, but is preferably from 1 second to 120 minutes, more preferably from 3 seconds to 30 minutes.

[0047] Post-curing varies depending on the heating conditions during molding, but is preferably carried out at 80–200°C, and more preferably at 100–180°C. The post-curing time varies depending on the heating conditions during molding, but is preferably 10–300 minutes, and more preferably 30–180 minutes.

[0048] Process (iii)

[0049] Next, a portion of the cured epoxy resin composition is ground to form a polished surface for forming the redistribution layer. Grinding can be performed on only one side of the sealant or on both sides. That is, if necessary, the redistribution layer can be formed on both sides of the sealant. At this time, it is preferable to grind the cured material until the Ra of the polished surface becomes 0.2 μm or less, and further, 0.15 μm or less. Grinding can be performed mechanically using a grinding machine such as a grinding wheel, or chemically.

[0050] Process (iv)

[0051] On the polished surface, a film of, for example, a coating material or a rewiring material is formed. The method for forming the coating material or rewiring material film is not particularly limited; examples include methods such as roller coating, screen coating, gravure coating, spin coating, die coating, and spray coating. Because of its high flatness, the polished surface allows for the easy formation of a coating material or rewiring material film with a uniform thickness. After forming the rewiring line (RDL), creating protrusions, etc., cutting can yield a monolithic device (electronic component mounting structure).

[0052] Next, the materials constituting the epoxy resin composition will be further described.

[0053] (Epoxy resin)

[0054] The epoxy resin included in the epoxy resin composition is not particularly limited, and may include bisphenol-type epoxy resins such as bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AD ​​type epoxy resin, and bisphenol S type epoxy resin; oligomer mixtures obtained by partial condensation of bisphenol-type epoxy resins; fluorene-type epoxy resins such as bisphenol fluorene type epoxy resin and biscresol fluorene type epoxy resin; naphthyl-type epoxy resins such as 1,6-bis(2,3-epoxypropoxy)naphthalene; biphenyl-type or tetramethylbiphenyl-type epoxy resins; aminophenol-type epoxy resins such as triglycidyl-p-aminophenol (p-aminophenol-type epoxy resin); aniline-type epoxy resins such as diglycidyl aniline; and toluidine-type epoxy resins such as diglycidyl o-toluidine. Glycidylamine epoxy resins, such as diaminodiphenylmethane type epoxy resins; alicyclic epoxy resins, such as dieoxylimonene type epoxy resins; dicyclopentadiene type epoxy resins; trimethylolpropane triglycidyl ether, trimethylolmethane triglycidyl ether, trimethylolethane triglycidyl ether, etc., trimethylolethane triglycidyl ether; polyether type epoxy resins; silicone-modified epoxy resins; phenolic varnish type epoxy resins; mononuclear aromatic epoxy resins with one benzene ring, such as catechol diglycidyl ether, resorcinol diglycidyl ether, phthalic acid diglycidyl ether, 2,5-diisopropylhydroquinone diglycidyl ether, and hydroquinone diglycidyl ether; and their nucleohydrogenated epoxy resins, etc. These can be used alone or in combination of two or more. Among these, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AD ​​type epoxy resin, naphthalene type epoxy resin, and phenolic varnish type epoxy resin are preferred, and bisphenol A type epoxy resin, bisphenol F type epoxy resin, and naphthalene type epoxy resin are more preferred, with naphthalene type epoxy resin being more preferred in terms of moisture resistance. They can be used alone or in combination of two or more.

[0055] In order to obtain a cured product with excellent heat resistance, moisture resistance, and electrical insulation properties, the epoxy resin content in the epoxy resin composition is preferably 1 to 30% by mass, more preferably 3 to 10% by mass.

[0056] (Fused silica)

[0057] In epoxy resin compositions, fused silica is included to suppress the thermal expansion coefficient of the cured epoxy resin composition to a low level. As fused silica, spherical fused silica, crushed fused silica, etc., can be used. From the perspective of flowability, spherical fused silica is preferred. The mainstream method for obtaining spherical fused silica is to melt pulverized silica powder in a high-temperature flame and spherize it by surface tension.

[0058] In spherical molten silica, hollow particles containing hollow sections are generated as a byproduct by incorporating gas during melting. The diameter of the pores originating from the cross-section of the hollow particles in the polished surface obtained by polishing the cured epoxy resin composition containing molten silica is also affected by the particle size of the molten silica. From the viewpoint of reducing the diameter of the pores originating from the cross-section of the hollow particles, the average particle size of the molten silica is preferably 10 μm or less, more preferably 7 μm or less. However, from the viewpoint of suppressing the high viscosity of the epoxy resin composition and increasing the content of molten silica, the average particle size of the molten silica is preferably greater than 1 μm, more preferably greater than 2 μm.

[0059] The average particle size of the molten silica contained in the epoxy resin composition before curing can be determined, for example, as the particle size (D50) at 50% of the cumulative volume of the volumetric particle size distribution. The average particle size (D50) can be determined by laser diffraction using a laser diffraction-type particle size distribution measuring device. Regardless of the properties of the epoxy resin composition before curing, the molten silica can be separated using a solvent that dissolves epoxy resin, etc.

[0060] Furthermore, from the viewpoint of reducing the diameter of the pores originating from the cross-section of hollow particles, the maximum particle size of molten silica is preferably 25 μm or less, more preferably 20 μm or less. It should be noted that, in the case of top-cut molten silica, the maximum particle size refers to the top-cut value.

[0061] The particle size of molten silica can be adjusted, for example, by using precise classification with wind power. Alternatively, highly selectively excluding particles with large hollow structures can be achieved through precise classification methods such as destructive classification and wet classification.

[0062] The content of molten silica in the epoxy resin composition is preferably 50-95% by mass, more preferably 70-90% by mass.

[0063] (Curing agent)

[0064] As a curing agent included in an epoxy resin composition, acid anhydride, phenolic resin, amine compound, etc. can be used.

[0065] As an acid anhydride, there are no particular limitations. Examples include phthalic anhydride, hexahydrophthalic anhydride, alkyl hexahydrophthalic anhydride (e.g., methyl hexahydrophthalic anhydride), tetrahydrophthalic anhydride, alkyl tetrahydrophthalic anhydride (e.g., 3-methyltetrahydrophthalic anhydride), trialkyltetrahydrophthalic anhydride, 5-norbornene-2,3-dicarboxylic anhydride, succinic anhydride, methylnadic anhydride, trimellitic anhydride, pyromellitic anhydride, and methylnorbornane-2,3-dicarboxylic acid. They can be used alone or in combination of two or more.

[0066] While there are no particular limitations on the phenolic resin used, phenolic varnish resins are preferred. Phenolic varnish resins are resins formed by the condensation polymerization of phenols or naphthols (such as phenol, cresol, naphthol, alkylphenol, bisphenol, terpene phenol, naphthol, etc.) with formaldehyde. More specifically, examples include phenolic varnish resins, cresol varnish resins, butylphenol varnish resins, alkylphenol varnish resins such as biphenol varnish resins, terpene phenol varnish resins, α-naphthol varnish resins, β-naphthol varnish resins, dicyclopentadiene cresol, poly(p-vinylphenol), bisphenol A type phenolic varnish, diphenyl dimethyl modified phenolic varnish, naphthane modified phenolic varnish, poly(di-o-hydroxyphenyl)methane, poly(di-m-hydroxyphenyl)methane, and poly(di-p-hydroxyphenyl)methane. Among these, naphthol varnish resins are preferred from the viewpoint of water resistance. They can be used individually or in combination of two or more.

[0067] As amine compounds, there are no particular limitations; for example, tetramethyldiaminodiphenylmethane, tetraethyldiaminodiphenylmethane, diethyldimethyldiaminodiphenylmethane, dimethyldiaminotoluene, diaminodibutyltoluene, diaminodipropyltoluene, diaminodiphenyl sulfone, diaminodimethylmethyl sulfone, diethyldiaminotoluene, bis(4-amino-3-ethylphenyl)methane, polytetramethylene oxide-di-p-aminobenzoate, etc., can be used. They can be used alone or in combination of two or more.

[0068] The curing agent is preferably used in an amount in which the number of functional groups of the curing agent is 0.05 to 1.5 equivalents, and further in an amount in the amount of 0.1 to 1.2 equivalents, relative to 1 equivalent of the epoxy group. As a result, the curability of the epoxy resin composition is improved, and the strength of the cured product is increased.

[0069] (other)

[0070] In addition to epoxy resin, fused silica, and curing agent, epoxy resin compositions may also contain curing accelerators, silane coupling agents, etc. Carbon black, defoamers, leveling agents, pigments, stress relievers, pregelatinizing agents, ion trapping agents, etc., may also be added in appropriate amounts depending on the purpose.

[0071] There are no particular limitations on the type of curing accelerator, and examples include imidazole-based curing accelerators, phosphorus-based curing accelerators, amine-based curing accelerators, organometallic compounds, phosphonium salt-based curing accelerators, bicyclic amidines and their derivatives, organometallic compounds or organometallic complexes, and urea compounds of polyamines. The curing accelerator preferably has latent properties. Examples of latent curing accelerators include imidazole-based accelerators, phosphorus-based accelerators, amine-based curing accelerators, and microencapsulated curing accelerators. When using a curing accelerator, the amount incorporated relative to 100 parts by weight of epoxy resin is preferably 0.1 to 40 parts by weight, more preferably 1 to 30 parts by weight.

[0072] Examples of imidazole-based curing accelerators include imidazole, 2-methylimidazole, 2-ethylimidazole, 1-isobutyl-2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1,2-dimethylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-phenylimidazole, and other 2-substituted imidazole compounds, as well as imidazole salts of 1-cyanoethyl-2-undecyltriphenyltrioxide and 1-cyanoethyl-2-phenyltriphenyltrioxide. Triazine adducts such as acid salts, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adducts, 2-phenylimidazolium isocyanuric acid adducts, 2-methylimidazolium isocyanuric acid adducts, 2-phenyl-4,5-dihydroxymethylimidazolium and 2-phenyl-4-methyl-5-dihydroxymethylimidazolium, etc.

[0073] Examples of phosphorus-based curing accelerators include trialkylphosphine compounds such as tributylphosphine and triarylphosphine compounds such as triphenylphosphine.

[0074] Examples of amine-based curing accelerators include 2,4,6-tris(dimethylaminomethyl)phenol, diethylamine, triethylamine, diethylenetetramine, triethylenetetramine, and 4,4-dimethylaminopyridine. Amine-based curing accelerators can also be amine adducts.

[0075] Examples of organometallic compounds or organometallic complexes include zinc naphthenate, cobalt naphthenate, tin octoate, cobalt octoate, cobalt diacetylacetonate (II), and cobalt triacetylacetonate (III).

[0076] As a microencapsulated curing accelerator, a particulate composition obtained by dispersing an amine compound powder in an epoxy resin can be used, for example. The amine compound can be selected based on the desired thickening ratio. Examples of amine compounds include aliphatic primary amines, alicyclic primary amines, aromatic primary amines, aliphatic secondary amines, alicyclic secondary amines, aromatic secondary amines, imidazole compounds, imidazole-line compounds, and reaction products of these compounds with carboxylic acids, sulfonic acids, isocyanates, or epoxy compounds. One or more of these compounds can be used. For example, aliphatic primary amines, alicyclic primary amines, aromatic primary amines, aliphatic secondary amines, alicyclic secondary amines, aromatic secondary amines, imidazole compounds, or imidazole-line compounds can be used in combination with the above reaction products. The average particle size of the amine compound powder is preferably 50 μm or less, more preferably 10 μm or less. Here, the average particle size is also calculated as the particle size (D50) at 50% of the cumulative volume of the volumetric particle size distribution. From the viewpoint of suppressing thickening at room temperature or 25°C, it is preferable that the amine compound powder has a melting point or softening point of 60°C or higher.

[0077] Silane coupling agents are formulated to react with the surface of molten silica and improve the dispersibility of molten silica in epoxy resin compositions. Silane coupling agents such as 3-epoxypropoxypropyltrimethoxysilane, 3-epoxypropoxypropyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, vinyltrimethoxysilane, and vinyltriethoxysilane can be used. They can be used alone or in combination of two or more. When using a silane coupling agent, the amount used is preferably 0.05 to 5 parts by weight, more preferably 0.1 to 3 parts by weight, relative to 100 parts by weight of molten silica.

[0078] (Preparation of epoxy resin composition)

[0079] The epoxy resin composition is preferably prepared by mixing the components in a specified ratio, for example, by stirring for 60 to 480 minutes, followed by degassing under reduced pressure before use. The epoxy resin composition can be in liquid or sheet form, or in a semi-cured state.

[0080] (Coating material)

[0081] The coating material, which is applied to the polished surface by coating or other methods, is not particularly limited and can be selected based on the intended use of the cured epoxy resin composition. When the epoxy resin composition is used as a sealing material for FOWLP or FOPLP, a surface protective film forming material can be selected as the material for forming redistribution wiring. Examples of surface protective film forming materials include photosensitive polyimide and photosensitive polybenzoxazole. The method for forming the film of the redistribution wiring forming material is not particularly limited; methods such as spin coating, die coating, spray coating, dipping, inkjet printing, screen printing, and jet dispensing can be used. After the coating is formed, a redistribution layer is formed by exposure, development, etching, or other processes. Alternatively, a seed layer (such as Cu) can be formed on the polished surface by sputtering or electroless plating, followed by patterning to form the redistribution layer. Cu, Cu alloys, Al, and Al alloys are preferred for the redistribution layer.

[0082] [Example]

[0083] The present invention will now be described in detail based on embodiments and comparative examples, but the present invention is not limited to the following embodiments.

[0084] [Example 1]

[0085] (1) Preparation of epoxy resin composition

[0086] The following substances were combined and stirred for 120 minutes, followed by degassing under reduced pressure to prepare an epoxy resin composition.

[0087] 100 parts by weight of epoxy resin

[0088] Bisphenol A type epoxy resin (manufactured by Nippon Kayaku Co., Ltd., RE-310, epoxy equivalent 184g / eq)

[0089] 100 parts by weight of curing agent

[0090] Methyltetrahydrophthalic anhydride (manufactured by Hitachi Chemical Co., Ltd., anhydride equivalent 164 g / eq)

[0091] 6 parts by weight of <curing accelerator>

[0092] Amine adduct-based latent curing accelerator (manufactured by AJINOMOTO CO.,INC., Amicure PN-23)

[0093] 3 parts by weight of <silane coupling agent>

[0094] 3-Epoxypropoxypropyltrimethoxysilane

[0095] 1 part by weight of carbon black

[0096] Made by Mitsubishi Chemical Corporation, #2600

[0097] 1500 parts by weight of <Fused Silica A>

[0098] The molten silica A used is silica that has been precisely graded to remove as many hollow particles as possible, with a maximum particle size set below 20 μm and an average particle size set at 4.5 μm. The maximum and average particle sizes were determined using a laser diffraction particle size distribution measuring device.

[0099] (2) Preparation of test pieces

[0100] The epoxy resin composition prepared in (1) was coated onto multiple monolithic semiconductor chips (1 mm thick) arranged on a resin film and then cured by compression molding. In the compression molding, the heating was set at 125°C for 10 minutes and the post-curing was set at 150°C for 1 hour.

[0101] (3) Grinding of the test piece

[0102] The surface of the cured material of the test piece prepared in (2) is ground with a grinding wheel to form a grinding surface.

[0103] (4) Evaluation

[0104] The polished surface of the cured specimen obtained in (3) was measured using an ultra-deep color 3D shape measuring microscope (KEYENCE CORPORATION, VK-9510). A photograph of the polished surface is shown below. Figure 1 In addition, a 25mm section was randomly selected from the grinding surface. 2 In 10 regions within the range, the diameter and number of pores originating from the cross-section of hollow particles were measured. The number of pores with diameters greater than 1.5 μm and less than 5 μm, pores with diameters greater than 5 μm and less than 10 μm, and pores with diameters greater than 10 μm were measured separately, and the average value was calculated. The results are shown in Table 1.

[0105] For the uneven, low-flatness sections (undulating portions) created by the holes, the diameter and depth of the largest observed hole, as well as the particle size of the hollow particles containing that hole, were measured. The arithmetic mean roughness (Ra), maximum height (Ry), and ten-point mean roughness (Rz) of the polished surface were then measured. The measurement distance was set to 100 μm. For the high-flatness sections (flat portions) without holes, the arithmetic mean roughness (Ra), maximum height (Ry), and ten-point mean roughness (Rz) were also measured in the same way. The results are shown in Table 2.

[0106] Then, photosensitive polyimide resin is coated onto the surface of the polished surface by spin coating, and exposed to form a cured film (the film thickness after curing is 5μm). The surface of the cured film is observed by electron microscopy (100x).

[0107] [Example 2]

[0108] Except that fused silica B was used as the fused silica, the epoxy resin composition was prepared in the same manner as in Example 1, and test pieces were made. The fused silica B used was silica that had been precisely graded to remove as many hollow particles as possible, with a maximum particle size set to 10 μm or less and an average particle size set to 3 μm. A photograph of the polished surface is shown below. Figure 2 The results of the evaluation of the polished surface are shown in Tables 1 and 2.

[0109] [Example 3]

[0110] Except that fused silica C was used as the fused silica, the epoxy resin composition was prepared in the same manner as in Example 1, and test pieces were made. The fused silica C used was silica that had undergone precise classification using wind power to remove as many hollow particles as possible, with a maximum particle size set to less than 10 μm and an average particle size set to 2 μm. A photograph of the polished surface is shown below. Figure 3 The results of the evaluation of the polished surface are shown in Tables 1 and 2.

[0111] [Comparative Example 1]

[0112] Except that fused silica D was used as the fused silica, the epoxy resin composition was prepared in the same manner as in Example 1, and test pieces were made. The fused silica D used was silica with a maximum particle size of less than 25 μm and an average particle size of 7 μm. A photograph of the polished surface is shown below. Figure 4 The results of the evaluation of the polished surface are shown in Tables 1 and 2.

[0113] [Comparative Example 2]

[0114] Except that fused silica E was used as the fused silica, the epoxy resin composition was prepared in the same manner as in Example 1, and test pieces were made. The maximum particle size of the fused silica E was less than 75 μm, and the average particle size was 20 μm. A photograph of the polished surface is shown below. Figure 5 The results of the evaluation of the polished surface are shown in Tables 1 and 2.

[0115] [Comparative Example 3]

[0116] Except that fused silica F was used as the fused silica, the epoxy resin composition was prepared in the same manner as in Example 1, and test pieces were made. The fused silica F was fused silica before fine grading of fused silica C. The maximum particle size of the fused silica F was 45 μm, and the average particle size was 2 μm. A photograph of the polished surface is shown below. Figure 6 The results of the evaluation of the polished surface are shown in Tables 1 and 2.

[0117] [Table 1]

[0118]

[0119] [Table 2]

[0120]

[0121] like Figure 1 , Figure 2 and Figure 3 As shown, pores originating from the cross-sections of hollow particles were also observed in the polished surfaces of the test pieces obtained in Examples 1, 2, and 3. However, all of these pores had a diameter of 5 μm or less. Since there were no pores with a diameter greater than 5 μm, the flatness of the polished surfaces was very high, as shown in Table 2. Furthermore, the surface of the photosensitive polyimide resin cured film formed on the polished surfaces was also confirmed to have very high flatness.

[0122] In the polished surfaces of the test pieces obtained in Comparative Examples 1, 2, and 3, there were pores with a diameter of less than 10 μm, and in particular, in Comparative Examples 1 and 3, there were also pores with a diameter of less than 5 μm. However, on the other hand, as... Figure 4 , Figure 5 and Figure 6 As shown in the figure, pores with diameters greater than 10 μm were also identified. Therefore, as shown in Table 2, the flatness of the polished surface is low. Furthermore, depressions were observed on the surface of the photosensitive polyimide resin cured film formed on the polished surface, indicating low flatness.

[0123] Industrial availability

[0124] The epoxy resin composition according to the present invention can form a highly flat polished surface when the cured material is polished, and a fine redistribution layer can be formed on the polished surface. The epoxy resin composition according to the present invention is useful as a sealing material for fan-out wafer-level packaging (FOWLP) or fan-out panel-level packaging (FOPLP).

[0125] Explanation of symbols

[0126] 1: The pores originating from the hollow particle cross-section observed in Example 1

[0127] 2: The pores originating from the hollow particle cross-section observed in Example 2

[0128] 3: The pores originating from the hollow particle cross-section observed in Example 3

[0129] 4: The pores originating from the cross-section of the hollow particle observed in Comparative Example 1

[0130] 5: The pores originating from the hollow particle cross-section observed in Comparative Example 2

[0131] 6: The pores originating from the hollow particle cross section observed in Comparative Example 3.

Claims

1. An epoxy resin composition comprising an epoxy resin, fused silica which may contain hollow particles, and a curing agent and / or a curing accelerator. The content of fused silica in the epoxy resin composition is 70-90% by mass. In the polished surface obtained by grinding the cured epoxy resin composition, at 25 mm 2 Within the observed range, the number of pores with a diameter greater than 5 μm originating from the cross-section of the hollow particles is one or less, and the polished surface is a polished surface polished until the arithmetic mean roughness Ra in the region without pores with a diameter greater than 1.5 μm becomes less than 0.2 μm. The cured product is formed by heat curing the epoxy resin composition at 150°C for 1 hour. The maximum particle size of molten silica is less than 25 μm, and the average particle size is greater than 1 μm but less than 10 μm. After the epoxy resin composition is cured, a portion of the cured material is ground until the arithmetic mean roughness Ra in the area without pores with a diameter greater than 1.5 μm becomes less than 0.2 μm, resulting in a ground surface, on which a redistribution layer is formed.

2. The epoxy resin composition according to claim 1, wherein, In the 25mm 2 The number of pores with a diameter greater than 2 μm from the cross section of the hollow particle observed within the range is less than one.

3. The epoxy resin composition according to claim 1 or 2, wherein it is a compression molding material for fan-out panel-level packaging or for fan-out wafer-level packaging.

4. An electronic component mounting structure, comprising: Electronic components, and Cured epoxy resin composition used to seal the electronic components. The epoxy resin composition comprises epoxy resin, fused silica which may contain hollow particles, and a curing agent and / or a curing accelerator. The content of fused silica in the epoxy resin composition is 70-90% by mass. The cured material has a polished surface that has been ground until the arithmetic mean roughness Ra in the region without pores larger than 1.5 μm in diameter is below 0.2 μm. In the grinding surface, at 25mm 2 Within the range, the number of pores with a diameter greater than 5 μm originating from the cross-section of the hollow particles observed was less than one. The maximum particle size of molten silica is less than 25 μm, and the average particle size is greater than 1 μm but less than 10 μm. A redistribution layer is formed on the polished surface.

5. A method for manufacturing an electronic component mounting structure, comprising the following steps: The process of preparing electronic components and the epoxy resin composition according to any one of claims 1 to 3; The process of sealing the electronic component with the epoxy resin composition and simultaneously curing the epoxy resin composition to form a sealed body comprising the electronic component and the cured epoxy resin composition; The process of forming a polished surface by grinding a portion of the cured material until the arithmetic mean roughness Ra in the region without pores larger than 1.5 μm in diameter is below 0.2 μm; and The process of forming a redistribution layer on the polished surface.

Citation Information

Patent Citations

  • Method for rewiring functional elements

    JP2013528318A

  • Adaptive patterning for panelized packaging

    CN102549732A

  • Semiconductor device and manufacturing meethod thereof

    CN1510745A

  • Method for forming light diffusion layer, light diffusion film and its manufacturing method, and ink jet device for light diffusion layer formation

    JP2004325861A

  • Resin composition

    JP2013173841A